A virtual reality approach to support Malaysian sign language interactive learning for deaf-mute children - Rahim, Nur Raidah; Abdul Rahim, Anis Amirah (ResearchTrentz Academy Publishing Education Services, 2022)
Malaysian Sign Language (MSL) is a primary sign language in Malaysia for the deaf-mute people including people with either hearing impairments or physically unable to speak. Communication is a main aspect that impacts the life of deaf-mute people. Learning MSL is very challenging as it is different from oral languages and has complex interpretation given the variability of size, shape and position of fingers or hand gestures. MSL is the only form of sign language that is recognized by the Malaysian Ministry of Education in formal education settings for deaf students. All teachings are provided visually, and students must be able to split their visual attention between signed narration and visual aids. Therefore, this paper presented a virtual reality (VR) approach to support MSL learning for deaf-mute children and their hearing parents. The VR application was assessed using a user acceptance test and pre-posttest. The findings showed that the VR application provides an innovative way for fast and efficient MSL learning compared to the conventional method.